Urgency of Reformulation of the National Development Planning System with the Gbhn Model - NOHANA, Ni Gek Ayu Septi; BAGIASTRA, I Nyoman (Protection: Journal Of Land And Environmental Law, 2023)
The discourse that has emerged in recent years regarding the importance of GBHN and plans to revive GBHN has surfaced. It is due to the less-than-optimal success of the national development planning system, which is a guideline for formulating long-term development plans (RPJP), medium-term development plans (RPJM) and annual development plans or Government Work Plans (RKP). However, the return of the GBHN concept has pros and cons; with the re-enactment of GBHN, it is feared that the authority of the MPR as the highest institution will re-emerge. Therefore, it is contrary to the presidential concept that has been agreed upon. Based on the above thinking, the main problem is how urgent the general boundaries of state policy are in the national development system. Second, How Compatible are the General Outlines of State Policy in the Indonesian Presidential System? In the context of formulation, discussion, and determination, the MPR must base it on the principle of the Democratic Directive Principle of State Policy Making, meaning that the formation of the basic policy must be carried out democratically, where the main feature of the democratic concept is public participation.